Comparative Pricing Analysis of Mecca's Religious Tourism - Ladki, Said (The international journal of religious tourism and pilgrimage, 2017)
This study compares the costing practices of three religious tourists groups. Specifically, the study compares the costs of Islamic religious tourism to Mecca among three groups: 1) Indonesia and India, 2) Lebanon and Tunisia, 3) Dubai and Qatar. The selection of the three groups was based on the following principle: Group 1: Represents the most populated and less affluent Islamic countries. Group 2: Represents the less affluent Arab States with moderate income Group 3: Represents the richest Arab Islamic countries in the world. Results indicate that countries with wealthy economies charge much higher prices for Hajj packages than those with moderate economies. However, the overall Hajj revenue is the highest ($940 millions) in the most populated Islamic countries (Indonesia). But for wealthy economies (Dubai) even though it's ranked as the fifth in the number of pilgrims, its revenues ($220,433,572) are high enough to be in the third place. Operators' pricing schemes fall into three independent categories: Competition-based Pricing, Consumer-based Pricing and Cost-based Pricing.